1987
DOI: 10.1088/0143-0815/8/4a/017
|View full text |Cite
|
Sign up to set email alerts
|

Impedance imaging in the newborn

Abstract: We have been investigating the use of electrical impedance methods for the study of cerebral haemodynamics in the newborn for many years. Of particular interest has been the early detection of intraventricular haemorrhage, which is a major cause of death or handicap in low birthweight infants. Several problems exist in obtaining representative impedance measurements from the newborn, most notably movement artefact, respiratory-based modulation and a blood-flow related pulsatile component. Movement artefact is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…These data were, however, significantly affected by artefacts. Murphy et al (1987) found that breathing movements and variations in cerebral blood flow caused the largest signal artefacts—up to 1% variation in their baseline signal at a frequency of approximately 0.5 Hz. The other significant artefact was synchronous with heart electrical activity, causing a variation of about 0.1% in signals.…”
Section: Introductionmentioning
confidence: 97%
“…These data were, however, significantly affected by artefacts. Murphy et al (1987) found that breathing movements and variations in cerebral blood flow caused the largest signal artefacts—up to 1% variation in their baseline signal at a frequency of approximately 0.5 Hz. The other significant artefact was synchronous with heart electrical activity, causing a variation of about 0.1% in signals.…”
Section: Introductionmentioning
confidence: 97%
“…EIT was briefly tested to the detection of neonatal intraventricular hemorrhage in the late 1980s [7], [8], with a result showing detection of ventricular bleeding in one neonatal patient. However, artifacts significantly affected these data.…”
Section: Introductionmentioning
confidence: 99%
“…If the latter restriction could be obviated, monitoring of the PEP would represent a valuable tool for applications in the central nervous system, as suggested previously, e.g., for the early detection of brain edema by monitoring of the conductivity [2], [3]. Other intracranial applications so far suggested refer to the monitoring of ventricular hemorrhage [4], [5], stroke, the evolution of spreading depressions, and epilepsy [6].…”
mentioning
confidence: 99%